PENGARUH PENGELOLAAN DANA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH BMT KUBE SEJAHTERA SURAKARTA - Suranto, Suranto (El-Hayah, 2018)
Abstract : This research aims at knowing: 1) the effect of fund management on customers’ loyalty at BMT Kube Sejahtera Surakarta; 2) the effect of promotion on customers’ loyalty at BMT Kube Sejahtera Surakarta; 3) the effect of service quality on customers’ loyalty at BMT Kube Sejahtera Surakarta; 4) the effect of fund management, promotion and service quality on customers’ loyalty at BMT Kube Sejahtera Surakarta.Research method applied was quantitative method. This research was conducted at BMT Kube Sejahtera Surakarta. Population of this research was all customers at BMT Kube Sejahtera Surakarta; 1506 people. This research used purposive sampling; sampling was 151 customers. Test of instrument use test of validity and reliability. Method of analyzing data used multiple linier regressions, test of classical assumption covering test of normality, multicoliniarity, heteroskedastic, F and t. The result of this research shows that 1) variable of fund management is value of tobserved = 8.370 more than ttable 1.980 and probability is 0.000 more or less 0.05. This indicates that fund management affects loyalty; 2) variable of promotion is value of tobserved = 2.107 more than ttable 1.980 and probability is 0.000 more or less 0.05. This means that promotion affects loyalty; 3) variable of service quality is value of tobserved = 3.761 more than ttable 1.980 and probability is 0.000 more or less 0.05. this shows that service quality affects loyalty; 4) Result of F test is Fobserved 33.322 more than Ftable 2.68 and sig. 0.000 more or less 0.05. This indicates that fund management, promotion, and service quality affect significantly on customers’ loyalty at BMT Kube Sejahtera Surakarta. Result of determination coefficient is R2 = 0.405 or 40.5%. It means that ability of independent variables covering fund management, promotion, and service quality explains dependent variable, loyalty, 40.5%. and the rest of 59.5% is affected by other variables outside this research. Similarity of multiple linier regression of this research is Y = 14,294 + 0,694 X1 + 0,120 X2 + 0,108 X3.Keywords: fund management, promotion, service quality, loyalty